THE ROLE OF RELIGIOUS AFFILIATION ON ATTITUDE TOWARDS PERSONS WITH DISABILITY IN ENUGU STATE, NIGERIA - Nwoko, Chrisanctus C. (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
There is growing concern about the attitudes of contemporary societies towards persons with disability. Observations indicate a wide variation in attitudes relative to disability in Nigeria regardless of their religious beliefs. Thus, the present study investigated the variations in attitude towards a person with a disability in Enugu State based on religious affiliations. The study adopted a cross-sectional research design. A convenient sample of two hundred and seventeen (n=217) respondents completed a self-report measure of the adapted version of the Attitudes towards Disabled Persons (SADP) scale. The result of the simple regression model revealed that the calculated value of F (1,215) = .461, P> .05 (.000) level of significance indicated a significant influence of religious affiliation on the level of attitude toward people with disability among the respondents. Most importantly, the finding revealed that religious affiliation contributed about 21.6% of the variation in attitude towards persons with disability. The finding has implications for disability policies.